2000
DOI: 10.1093/chemse/25.2.141
|View full text |Cite
|
Sign up to set email alerts
|

The Plant Sesquiterpene Germacrene D Specifically Activates a Major Type of Antennal Receptor Neuron of the Tobacco Budworm Moth Heliothis virescens

Abstract: Plants release hundreds of volatiles that are important in interactions with insects or other organisms. However, knowledge is scarce as to which of the compounds are detected by the organism's olfactory receptor neurons. In the present study, single receptor neurons on the antennae of the tobacco budworm moth, Heliothis virescens, were screened for their sensitivities to naturally produced plant volatiles by the use of gas chromatography linked to electrophysiological recordings from single cells (GC-SCR). Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 28 publications
0
50
0
2
Order By: Relevance
“…6,8 E). Other authors found high specificity in pheromone-processing AL neurons Hartlieb et al, 1997;de Bruyne et al, 2001) or ORCs responsive to plant volatiles (Hansson et al, 1999;Røstelien et al, 2000;Angioy et al, 2003) only at low, natural stimulus intensities. These findings, together with ours, illustrate the importance of testing odor stimuli over a range of concentrations to characterize the MRRs of olfactory neurons.…”
Section: Discussionmentioning
confidence: 94%
“…6,8 E). Other authors found high specificity in pheromone-processing AL neurons Hartlieb et al, 1997;de Bruyne et al, 2001) or ORCs responsive to plant volatiles (Hansson et al, 1999;Røstelien et al, 2000;Angioy et al, 2003) only at low, natural stimulus intensities. These findings, together with ours, illustrate the importance of testing odor stimuli over a range of concentrations to characterize the MRRs of olfactory neurons.…”
Section: Discussionmentioning
confidence: 94%
“…Eugenol, as one of the phenolic compounds characteristic of basil volatile oil, shows antioxidant (Juliani and Simon 2002) and antimicrobial activity (Ali et al 2005). Germacrene C and D, components from the group of sesquiterpene hydrocarbons, exhibit antimicrobial and insecticidal activity (Røstelien et al 2000;Stranden et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This compound was one of the plant second metabolisms known as an essential oil, which was also a volatile with ecological function involved in the interaction among plant insect enemy (Røstelien et al 2000). Germacrene D synthase belonged to the terpene synthase family, and several germacrene D synthase genes had been identified from plants such as Vitis vinifera, Actinidia deliciosa and Zingiber officinale (Lücker et al 2004;Picaud et al 2006).…”
Section: Resultsmentioning
confidence: 99%